Corporal diagnostic work and diagnostic spaces: clinicians' use of space and bodies during diagnosis. Issue 5 (13th February 2015) - Gardner, John; Williams, Clare
Abstract An emerging body of literature in sociology has demonstrated that diagnosis is a useful focal point for understanding the social dimensions of health and illness. This article contributes to this work by drawing attention to the relationship between diagnostic spaces and the way in which clinicians use their own bodies during the diagnostic process. As a case study, we draw upon fieldwork conducted with a multidisciplinary clinical team providing deep brain stimulation (DBS) to treat children with a movement disorder called dystonia. Interviews were conducted with team members and diagnostic examinations were observed. We illustrate that clinicians use communicative body work and verbal communication to transform a material terrain into diagnostic space, and we illustrate how this diagnostic space configures forms of embodied 'sensing‐and‐acting' within. We argue that a 'diagnosis' can be conceptualised as emerging from an interaction in which space, the clinician‐body, and the patient‐body (or body‐part) mutually configure one another. By conceptualising diagnosis in this way, this article draws attention to the corporal bases of diagnostic power and counters Cartesian‐like accounts of clinical work in which the patient‐body is objectified by a disembodied medical discourse.